2013
DOI: 10.1002/bdrb.21061
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Prevents Ethanol‐Induced Developmental Anomalies in Cultured Mouse Fetus through Multiple Activities

Abstract: This study revealed that cotreatment with emodin significantly prevented teratogenesis induced by ethanol, not only by modulating hypoxia and antioxidant enzymes, but also by attenuating the enhanced levels of TNF-α and caspase 3 in cultured embryos. Therefore, emodin may be an effective preventive agent for ethanol-induced teratogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Emodin possesses antioxidative activities including increased superoxide dismutase (SOD) activity, and SOD1, SOD2, and cytosolic glutathione peroxidase mRNA as well as anti-inflammatory activities. Also, emodin inhibited 5α-reductase by the hydroxyl group and attenuated the PGD2 activities by blocking NF-κB, a major transcription factor for COX-2 in a dose dependent manner [3,9,22]. Therefore, based on the results of the present study, we can infer that emodin may act via inhibitions of 5α-reductase and PGD2 activities, as well as through antioxidative and anti-inflammatory activities.…”
Section: Discussionsupporting
confidence: 56%
“…Emodin possesses antioxidative activities including increased superoxide dismutase (SOD) activity, and SOD1, SOD2, and cytosolic glutathione peroxidase mRNA as well as anti-inflammatory activities. Also, emodin inhibited 5α-reductase by the hydroxyl group and attenuated the PGD2 activities by blocking NF-κB, a major transcription factor for COX-2 in a dose dependent manner [3,9,22]. Therefore, based on the results of the present study, we can infer that emodin may act via inhibitions of 5α-reductase and PGD2 activities, as well as through antioxidative and anti-inflammatory activities.…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, emodin may be considered a potential lead therapeutic to treat SARS . Another study revealed that co-treatment with emodin (1 Â 10 À 5 and 1 Â 10 À 4 μg/ml) significantly prevented ethanol-induced developmental anomalies in cultured mouse fetuses by modulating hypoxia and antioxidant enzymes and attenuating the enhanced levels of TNF-α and caspase 3 in cultured embryos (Yon et al, 2013). Emodin (1 μM to 10 μM) also inhibited tonic tension in a concentration-and time-dependent manner by suppressing the PKCδ-mediated inhibition of myosin phosphatase in isolated rat thoracic aortas (Lim et al, 2014).…”
Section: Other Pharmacological Effectsmentioning
confidence: 99%
“…The pharmacological effects of stilbene in Polygonum multiflorum have been reported to promote anti-aging effects (Long and Dougherty, 2003;Lin et al, 2008;Chen et al, 2001a;Chan et al, 2002;Um et al, 2006;Cheung et al, 2014) and hepatoprotective activities (Huang et al, 2007;Liu et al, 1992). Anthraquinones, another main component of this plant, also have many biological activities, such as effects against cancer (Ma et al, 2012;Wang et al, 2011b;Way et al, 2014;Yu, et al, 2013;Lin et al, 2006;Tabolacci et al, 2010), developmental anomalies (Yon et al, 2013), and tonic tension (Lim et al, 2014). However, an increasing number of recently published studies have demonstrated the adverse effects of Polygonum multiflorum.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the decreased level of TNF-α after GM-CSF treatment was essential mechanism of action against hypothyroidism. In addition, TNF-α was found to increase apoptotic mechanisms in embryo [54]. The immunoprotective action of GM-CSF could ensure immune system homeostasis and decrease the vulnerability to stress-induced disease (7).…”
Section: Discussionmentioning
confidence: 97%